Characterization of Proximal Small Intestinal Microbiota in Patients With Suspected Small Intestinal Bacterial Overgrowth: A Cross-Sectional Study. Issue 8 (August 2019) - Shin, Andrea S.; Gao, Xiang; Bohm, Matthew; Lin, Huaiying; Gupta, Anita; Nelson, David E.; Toh, Evelyn; Teagarden, Sean; Siwiec, Robert; Dong, Qunfeng; Wo, John M.
Abstract : OBJECTIVES: The composition of the small intestinal microbiota has not yet been characterized thoroughly using culture-independent techniques. We compared small intestinal microbial communities in patients with and without small intestinal bacterial overgrowth (SIBO) using culture-dependent and culture-independent bacterial identification approaches. METHODS: Small bowel aspirate and mucosal samples were collected from patients with suspected SIBO. The aspirates were cultured to diagnose SIBO, defined as ≥10 4 colony-forming units/mL coliform or ≥10 5 colony-forming units/mL upper aerodigestive tract bacteria. Bacteria in the aspirates and mucosa were identified using 16S rRNA gene sequencing. We compared small intestinal microbiome composition between groups with and without a culture-based SIBO diagnosis. RESULTS: Analysis of the aspirate and mucosal microbial communities from 36 patients revealed decreased α-diversity but no differences in β-diversity in patients with SIBO compared with those without SIBO. There were no significant differences in the relative abundance of individual taxa from the aspirates or mucosa after adjustment for false discovery rate between patients with and without SIBO. Subgroup analysis revealed significant differences in mucosal β-diversity between the coliform and upper aerodigestive tract subgroups. Relative abundances of a mucosal Clostridium spp. ( P = 0.05) and an aspirate Granulicatella spp. ( P = 0.02) were higher in coliform SIBO vs non-SIBO subgroups. The microbial composition and relative abundance of multiple taxa significantly differed in the mucosal and aspirate specimens. DISCUSSION: Culture-based results of small bowel aspirates do not correspond to aspirate microbiota composition but may be associated with species richness of the mucosal microbiota.